A case of forensic genomics in Uganda reveals animal ownership and low exotic genetic introgression in indigenous cattle - Masembe, Charles; Benda, Kirungi Katali; Opoola, Oluyinka; Ndinawe, Ruth Pamela; Beine, Peter; Mukiibi, Robert (Veterinary Medicine and Science, 2023)
The cattle industry contributes to Uganda's agricultural output. It faces challenges that include theft and parentage ascertainment. These challenges can benefit from recent molecular genomics and bioinformatics technologies. We employed genomic analyses to establish potential ownership of a group of nine cattle that were being claimed by two farmers in Uganda. We investigated the genetic relationship of Ugandan cattle with regional indigenous breeds as well as exotic breeds that are currently present in Uganda. In addition, we investigated regions that are likely to be under selection in the Ugandan cattle. Hair samples were collected from seven and two animals from farmers A and B, respectively. They were genotyped for 53,218 Single Nucleotide Polymorphism markers. To establish genetic relationships between the sampled animals, we performed genomic analyses including, principal component analysis (PCA), hierarchical clustering analysis and identity by state/descent. We also performed admixture and runs of homozygosity analyses to assess the ancestry composition and identify regions potentially under selection in Ugandan cattle, respectively. The seven animals from Farmer A were genetically close to each other but showed minimal relationship with the disputed animals. The two animals from Farmer B were genetically distant from each other but showed greater similarity to four of the disputed animals. Four of the disputed animals showed great dissimilarity from the animals of both farmers. Comparison of these with the reference breeds revealed minimal European exotic genetic introgression into these animals, but rather high similarity to the Sheko. Results also revealed high homozygosity in the major histocompatibility complex regions. Our results demonstrate the use of currently available genomic tools to empirically establish the ownership of cattle; these could be scaled up as a resourceful and viable tool that could be employed to support conflict resolution where reliable livestock identification is unavailable.